Implementation of Engineering Everywhere in Physics LKPD Based on STEM Approach to Improve Science Process Skills - Zainuddin Zainuddin*; Muhammad Syukri; Soni Prayogi; Safira Luthfia (Jurnal Pendidikan Sains Indonesia, 2022)
High school students (MAN 3) Banda Aceh are experiencing problems related to science process skills, so they need to be improved. Efforts to improve KPS can be pursued through "Implementation of Engineering Everywhere in Physics worksheets based on the STEM approach with the aim of knowing the improvement of students' science process skills using Engineering Everywhere on physics worksheets based on the STEM approach. The Pre-Experimental Design One Group Pretest-Postest research, research subjects for class XI MIA 2 students as many as 27 people. The instruments used consisted of test instruments (scientific process skills test questions), and non-tests (RPP, LKS, teacher observation sheets, and student response questionnaires). Data analysis techniques quantitatively and qualitatively as well as the calculation of the N-Gain Score. The results of qualitative data analysis obtained validity, practicality of the instruments used and quantitative data analysis obtained the effectiveness of the science process skills instrument with an N-gain result of 0.69, and was supported by the results of the student response questionnaire which scored 940 in the effective category